Creating and evaluating the score to assess overdose: the OD score - Kazuki Nagashima; Nobuhiro Yasuno; Machiko Watanabe (BMC Emergency Medicine, 2024)
Abstract Background During disasters (including epidemics such as coronavirus disease 2019), the capacity of emergency departments is exceeded, thereby hindering the administration of appropriate lifesaving measures. Furthermore, the number of overdose patients increases because of the stress overload during emergency situation. The fact that overdose patients are forced to be transported to medical facilities that do not typically treat them is becoming worrisome. Moreover, there is no definitive score for overdose. This study aimed to create a patient-specific scoring system to assess overdose. Methods This was a retrospective single-center study. The evidence-based OD score was evaluated on a scale of 0–15. Further, logistic analysis and receiver operating characteristic (ROC) curve analysis were performed to evaluate the score. Results Overall, 262 patients (including 118 overdose patients) receiving care at the intensive care unit of Japan’s Teikyo University Hospital in 2021 were targeted. Regarding the total OD score, ROC analysis revealed a cutoff of 8 (area under the curve [AUC]: 0.99, 95% confidence interval [CI]: 0.980–0.997, sensitivity: 0.95, specificity: 0.95, p < 0.05), which was considered to indicate an overdose. Of the items evaluated in the OD score, the scenario at the location of the patient’s discovery (adjusted odds ratio [AOR]: 16.8, 95% CI: 5.0–255.9, p = 0.002) and recent experience of mental anxiety (AOR: 55.7, 95% CI: 2.8–5399.5, p = 0.03) significantly predicted an overdose in multivariable logistic regression analysis. External validation revealed that the OD score could also identify overdose in patients treated in a cohort from 2022 (average cutoff: 8.6, average AUC: 1.0, p < 0.0001). Conclusions The OD score could accurately assess overdose patients. Medical facilities that do not frequently address overdose patients will benefit from the use of this score.